Analysis of railway public policy in the La Dorada to Chiriguana project. in Colombia (2020)
The origins of public policies are generally summarized with the creation of the so-called welfare state in the twentieth century, and with the differences between Politics (politics), policies (policies) understanding the first as the relations of power in government, and the second are the actions, omissions and decisions, to analyze public policies you have to understand their cycle which is formed by the problem, inclusion in the agenda, policy formulation, decision, implementation and finally evaluation. The railway in Colombia began in Panama when it was built in 1855 and in its greatest splendor the network reached more than 3,300 km, from then on it was abandoned by the different governments, until a problem in efficiency was detected. of transportation in Colombia and it was decided to reactivate the railway using it as part of the intermodal transport within the master transport plan (PMTI) 2015 - 2035 where the railway project between La Dorada and Chiriguaná is located to connect the center of the country with the port of Santa Marta. The section between La Dorada and Chiriguaná consists of a distance of 522 kms and an approximate budget of 0.7 billion pesos, since the decision that was made was to rehabilitate the existing road in its entirety using the same route and gauge being These are the main problem of this project, where different actors interfere, such as public and private, individual and collective, and because of their influence, this decision. The decision to adopt intermodal transport as a solution to the transportation problem in Colombia presents certain difficulties due to the costs and the greater infrastructure that it requires for its operation, in addition to the decision to use the same routes and the gauge in the case Railway does not allow efficient use of these due to technical limitations.